AERIAL PHOTOGRAPHY USING UNMANNED AERIAL VEHICLE (UAV) FOR TOPOGRAPHIC MAPPING AND DAM ANALYSIS (CASE STUDY: KARANGNONGKO DAM PACKAGE ONE) - Shafa Nabila Prawitasari; Ayu Raina Nabilah (Journal of Marine-Earth Science and Technology, 2024)
Water is a natural resource that is crucial for survival and various industrial, fishery, and agricultural activities. In the use of water, there is often a lack of care in its use and utilization so that efforts are needed to maintain a balance between the availability and needs of water through development, conservation, improvement and protection. The construction of dams, such as the Karangnongko Dam, aims to improve community welfare by providing irrigation water and raw water, as well as potential as a tourist destination. Visualization of the Slope Map, Aspect Map, and Contour Map shows the progress of the Karangnongko Dam construction in August 2024. These maps indicate the dominance of flat areas, the direction of the excavation tends to the northwest, and the contours are tight at the edges and looser in the middle area of the dam.